Caregiving for Epilepsy: Awareness, Knowledge, Attitude and Health-Related Quality of Life of Family Caregivers - Pei Lin, Lua; Nor Khaira Wahida, Khairuzzaman; Zariah, A; K.F., Lee (2014)
Living with epilepsy is equally demanding for both patients and their caregivers. The caregivers’ tasks are not limited to caring for the patients only but also the need to improve their awareness, knowledge and attitude (AKA) level as lack of understanding has a major impact on health-related quality of life (HRQoL). Little is known about the influence of AKA on family caregivers’ HRQoL. Objective: Therefore, this study aimed to assess and relate the AKA and HRQoL profiles of epilepsy carers. Methods: This prospective, cross-sectional study included a sample of 32 epilepsy family caregivers who were recruited from the Neurology and Paediatric Clinics of Hospital Sultanah Nur Zahirah (HSNZ), Kuala Terengganu. Results: Majority were Muslims (93.8%), married (65.6%), housewives (31.2%), who earning monthly income of not more than RM 1000 (34.4%) and was the patients’ mothers (40.6%). The Total AKA score was generally good (mean=123.4±16.8, median 122.5) with awareness being good, knowledge moderate and attitude positive whereas HRQoL score for Disruptiveness was the highest (good) compared to other domains. There were significantly higher scores for Sexual Functioning (p = 0.039) among Poor AKA group and Pain Management (p = 0.040) among Good AKA. Conclusion: The overall outcomes signified that family caregivers with Good AKA experienced better well-being compared to those with Poor AKA while carrying out their roles as caregivers. Consequently, carers clearly require constant epilepsy education to enhance skill-building in order to understand and keep updates with the disease, thus indirectly sustaining their desired HRQoL status from time to time.